Utility of 1% Tropicamide in Improving the Quality of Images for Tele-Screening of Diabetic Retinopathy in Patients with Dark Irides. (4th July 2017) - Banaee, Touka; Ansari-Astaneh, Mohammad-Reza; Pourreza, Hamidreza; Faal Hosseini, Fatemeh; Vatanparast, Maryam; Shoeibi, Nasser; Jami, Vajihe
ABSTRACT: Purpose : To compare the quality of fundus photographs taken before and after instillation of one drop of tropicamide. Methods : The 45º fundus photographs were taken with a non-mydriatic fundus camera in three conditions of the pupil; pre-mydriatic, 10 minutes after one drop of tropicamide, and fully dilated. Two photographs were taken in each condition; one centered on the macula and the other on the optic disc. Two vitreoretinal specialists graded the images. Results : A total of 1768 fundus photographs of 149 diabetic patients with dark irides were included. There were more ungradable images (38.1% and 50.3%, graders 1 and 2, respectively) in the non-mydriatic state than partially- (4.6% and 11.5%) or fully-dilated (15.4% and 10.0%) conditions ( p < 0.001, both graders). Partially and fully dilated states had similar rates of ungradable images ( p = 0.56 and p = 0.54, graders 1 and 2, respectively). Test–retest reliability (repeatability) was 92.5% and 74.3% for the two graders, respectively. Inter-grader agreement was moderate (Kappa = 0.50). Conclusion : Non-mydriatic fundus photographs have a high rate of ungradable images in patients with dark irides. Instillation of only one drop of tropicamide improves the quality of fundus photographs, which is not furthered by adding more drops. This strategy can be used in tele-ophthalmology programs.